Bacaan basmalah dalam sholat perspektif ulama mazhab empat - Umam, Rosyidul; Yazid Adnan Quthny, Abu (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2023)
This paper discusses a comparative study of the madhhabs of reciting the basmalah in prayer from the perspective of the four madhhabs. Regarding basmalah, the scholars agree that basmalah is one of the verses of Surah al-Naml. But they differ in opinion about reading basmalah at the beginning of the recitation of the Qur'an in prayer. The difference in reading the basmalah when praying has made Muslims divided, and even more concerning, there is an assumption that people who are accustomed to reading the basmalah in prayers in mosques and musholla whose imams do not read the basmalah have invalid prayers. What actually causes this difference? What is the perspective of the four madzhab scholars on this issue? Collecting data used in the preparation of this thesis, the author uses library research by referring to primary sources known from fiqh books, namely Madzahibul Arba'ah, while secondary data is a supporter that still has relevance to the discussion of this journal. In compiling and completing it, the author uses an analytical descriptive method through data collection and the opinions of the scholars to then draw a conclusion. This research leads to the conclusion that what causes differences among scholars related to the recitation of basmalah during prayer is the variety of fiqh sciences that contradict each other, differences in determining the position of basmalah in the Qur'an, and differences in fiqh sciences related to this issue.